2012
DOI: 10.1159/000338163
|View full text |Cite
|
Sign up to set email alerts
|

The Opioid System and Food Intake: Homeostatic and Hedonic Mechanisms

Abstract: Opioids are important in reward processes leading to addictive behavior such as self-administration of opioids and other drugs of abuse including nicotine and alcohol. Opioids are also involved in a broadly distributed neural network that regulates eating behavior, affecting both homeostatic and hedonic mechanisms. In this sense, opioids are particularly implicated in the modulation of highly palatable foods, and opioid antagonists attenuate both addictive drug taking and appetite for palatable food. Thus, cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 121 publications
3
85
1
5
Order By: Relevance
“…The magnitude of these effects was large enough such that, under naloxone, there was no clear preference for either food type. Our experiments converge with lines of preclinical and clinical data suggesting the EOS mediates aspects of hedonic feeding [10,16,19,20,23,29,30].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The magnitude of these effects was large enough such that, under naloxone, there was no clear preference for either food type. Our experiments converge with lines of preclinical and clinical data suggesting the EOS mediates aspects of hedonic feeding [10,16,19,20,23,29,30].…”
Section: Discussionsupporting
confidence: 84%
“…It has also been suggested that opioids mediate eating that occurs outside of caloric needs, or hedonic feeding [19,29,30]. Opioid receptor agonists tend to produce increases in food intake in animals while opioid receptor antagonists mostly show inhibitory effects [31][32][33], but these affects appear to be sensitive to the overall palatability of the reinforcer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this plausible explanation, we propose that the weight loss is not due solely to withdrawal or alterations in food/fluid consumption. 79,80 Hook and colleagues have shown that a single intrathecal administration of morphine produces lasting weight loss in rats. 39,40 This weight loss cannot result from withdrawal, and acute administration of morphine does not significantly affect food intake.…”
Section: Fig 13mentioning
confidence: 99%
“…This study was conducted on healthy subjects aged 18-44 years, because this age group is active and productive and has not yet undergone the changes in β-endorphin metabolism that occur in the elderly [9]. This study also limited the consumption of foods and medications that may affect β-endorphin levels [10,11]. Subjects with a BMI of 18.5-25 were part of the inclusion criteria to reduce the likelihood of metabolic differences that may affect β-endorphin levels [12,13].…”
Section: Discussionmentioning
confidence: 99%